Blood of Mugwump : A Tiresian Tale of Incest - Rice, Doug (Black ice books., 2016)
Rice's parasitical language is akin to the acts of those naked 18th century pirates of desire. In Blood of Mugwump Rice cannibalizes the likes of Joyce, Faulkner, Burroughs, Eliot, and a whole host of dead angelic others. Now trapped inside a kinetic body that is always changing from male to female, Doug Rice (the youngest Mugwump) sets out to discover himself in his sister's body. All the while the familial matriarch, Grandma Mugwump, feeds on the flesh of young Doug. Once through the looking glass, Doug realizes that Caddie (his polysexual Faulknerian nightmare of a sister) is more terrifying and holy than the average saint. A frenzied sexual virus, genetically conveyed, mutates and possesses the meat of Doug's and Caddie's bodies forcing them to love each other in unspeakable, yet classical, ways.